THE IDENTITY OF MUDMEE SILK PATTERNS: CULTURAL WISDOM HERITAGE OF KHON KAEN FOLKLORE MASTERS - Chaijan, Khunyarin (Srinakharinwirot Research and Development Journal of Humanities and Social Sciences, 2024)
This research studies the identity and symbols patterns of traditional Mudmee silk and applied Mudmee silk patterns, and the interpretation of mudmee silk patterns in the context of folklore masters in Chonnabot District, Khon Kaen Province by qualitative research, in-depth interviews, participant observation of stakeholders and documentary research analysis. Purposive sampling was used to select well-known regional folklore masters in the area aged over 40 with over 20 years of continuous experience in making Mudmee silk. The goal swas to compile a significant database of Mudmee silk patterns by folklore masters as intangible cultural heritage to add value to local culture in future. Results were that Chonnabot District was considered the center of Mudmee silk in Khon Kaen Province. Nationally recognized Mudmee silk has been registered by geographical indication (GI). The identity of Mudmee silk consisted of patterns and weaving techniques. Creation of Mudmee silk patterns by folklore masters was seen as craft wisdom requiring skill and accumulated experience to achieve proficiency. Pattern identities inherited and considered as prototypes of the Madmee silk of Chonnabot District included Kong, Khan Mak Beng, Phra Thep, and Choeng Thian. Original unique colors included tamarind seed, red, purple, and green. The current identity of Mudmee silk patterns results from applying traditional patterns, drawing inspiration from surroundings, lifestyles, the environment, plants and animals, tools, appliances, and jewelry, media, religious beliefs, and local identities. These lead to development of a range of multidimensional colors.